KEANEKARAGAMAN JENIS TANAMAN BUNGA DI PEKARANGAN DESA MANDIKAPAU BARAT KABUPATEN BANJAR - Nur Riyani; Anang Kadarsah; Aminuddin Prahatama Putra (Universitas Lambung Mangkurat, 2023)
Plant diversity indicates the existence of various variations in shape, color, body structure, and the amount contained in an area or ecosystem. The purpose of this study was to describe the types and number of index values for the diversity of types of flower plant in the yards of the residents of Mandikapau Barat Village. The method of this research was to determine the location by means of a survey, determine the area of the yard, take samples by purposive sampling technique, identify the types of flower plant using plant morphology book, and conduct data analysis by calculating the importance value index, species diversity index, dominance index, and abundance index. type. The results of this study found that there were 60 types of flower plant with an average abundance of 1087 ind/m² and 34 famili; RT 1 (26 species with an average abundance of 317 ind/m² and 20 famili); in RT 2 (26 species with an average abundance of 318 ind/m² and 22 famili); and in RT 3 (49 species with an average abundance of 452 ind/m² and 30 famili). The types of flower plant that were mostly found in RT 1 were dahlia flowers (Zinnia elegans L.) 16.72%; in RT 2, namely dahlia flowers (Zinnia elegans L.) 21.70%; and in RT 3, namely linjuang (Cordyline fruticosa L.) 14.38%. Plant in the tree ornamental plant category were 1.7%, leaf ornamental plant were 13.3%, and flower ornamental plant were 85%. The overall value of the diversity index of flower plant is 2.71, which is in the medium category. The overall value of the domination index of 0.1 for flowering plant is in the low category. The overall value of the abundance index of types of flower plant is 0.78, belonging to the high category. The overall value of the important value index of 0.67% for flowering plant is classified in the high category.